Prototype Motion Sensor And Automatic Locking Based On The Internet Of Things (IOT): Prototype Motion Sensor And Automatic Locking Based On The Internet Of Things (IOT) - Choiriah, Wirdah; Putra Pane, Eddissyah; Roki Hardianto; Eva Tri Ningsih (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
The application of IoT in remote control systems to home security is becoming a necessity. This research designed 2 parts of the application of IoT, namely the automatic locking control system and motion sensor detection. With IoT, it can help reduce the risk of laziness in households. The equipment used in the IoT circuit is the nodemcu esp8266 internet module, 5vdc relay module, electrical sockets and pitting and cellphone chargers. The way this electrical IoT works is by controlling it from a smartphone that is connected to a device using applications and the internet. With a note on the IoT tool at home, there is already a living internet network. If the internet network has a problem, the tool will not work properly. The output of this research is a Control System IoT product in the form of a prototype that can be used for the motion detection process and an IOT-based door locking system that can be controlled from a smartphone